2014
DOI: 10.1007/s10992-014-9342-6
|View full text |Cite
|
Sign up to set email alerts
|

The Logics of Strict-Tolerant Logic

Abstract: Adding a transparent truth predicate to a language completely governed by classical logic is not possible. The trouble, as is well-known, comes from paradoxes such as the Liar and Curry. Recently, Cobreros, Egré, Ripley and van Rooij have put forward an approach based on a non-transitive notion of consequence which is suitable to deal with semantic paradoxes while having a transparent truth predicate together with classical logic. Nevertheless, there are some interesting issues concerning the set of metainfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
114
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(117 citation statements)
references
References 24 publications
1
114
0
2
Order By: Relevance
“…The second point concerns the status of a theory based on ST as a distinctive approach to paradoxes. The connections shown by Barrio et al (2015) and Dicher and Paoli (2019) between ST and LP ground their claim that ST is nothing more than LP in sheep's clothing. Although a proper assessment of their arguments is outside the scope of this paper, the fact that we can represent xy-unsatisfiability, xy-supersatisfiability and xy-antivalidity of an inference in terms of the xy-validity of a metainference shows that all these logics are connected by different symmetries to one another.…”
Section: Final Remarksmentioning
confidence: 79%
See 2 more Smart Citations
“…The second point concerns the status of a theory based on ST as a distinctive approach to paradoxes. The connections shown by Barrio et al (2015) and Dicher and Paoli (2019) between ST and LP ground their claim that ST is nothing more than LP in sheep's clothing. Although a proper assessment of their arguments is outside the scope of this paper, the fact that we can represent xy-unsatisfiability, xy-supersatisfiability and xy-antivalidity of an inference in terms of the xy-validity of a metainference shows that all these logics are connected by different symmetries to one another.…”
Section: Final Remarksmentioning
confidence: 79%
“…Comparing trees for LP-inferences and trees for STmetainferences, we can see that there's a correspondence between the two logics. A metainference is ST-valid just in case the result of "lowering" it to an inference (that is, substituting '⇒' by '⊃' and ' ' by '⇒') is LP-valid (this connection was noticed and proved in Barrio et al (2015)). An analogous correspondence connects TS metainferences to K3 inferences (see Cobreros et al (2019) for more on this).…”
Section: Trees For Metainferencesmentioning
confidence: 94%
See 1 more Smart Citation
“…About these logics we shall mention, in addition to the previous remarks, that in [4], [11] and [25] it is shown that-through some suitable translation-the set of valid inferences in LP coincides with the set of valid meta-inferences in ST, while in [14] it is conjectured that-again, through some suitable translation-the set of 8 By these rules we refer to the following, respectively.…”
Section: Definition 315 ([8] [21]) a 3-valued Ts-matrix Is A Q-matrixmentioning
confidence: 92%
“…A third and final issue I will mention is that, due to the fact that in substructural logics there is a splitting of the notion of consequence into an internal and an external component (see for instance Mares & Paoli 2014;Avron 1988;Barrio, Rosenblatt, & Tajer 2015), perhaps there should be a corresponding distinction in the definition of internalization. More precisely, since there are two notions of consequence, there should be two validity predicates, one to capture each notion.…”
mentioning
confidence: 99%